Inspiration from Nature: Influence of Engineered Ligand Scaffolds and Auxiliary Factors on the Reactivity of Biomimetic Oxidants - Gourab Mukherjee; Jagnyesh K. Satpathy; Umesh K. Bagha; Chivukula V. Sastri; Sam P. de Visser; Muhammad Qadri Effendy Mubarak (American Chemical Society Publications, 2024)
Indexed by WOS/Scopus/ERA